2017
DOI: 10.18632/oncotarget.15125
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of apoptotic pathways by SMAC or BH3 mimetics distinctly sensitizes paclitaxel-resistant triple negative breast cancer cells

Abstract: Standard chemotherapy is the only systemic treatment for triple-negative breast cancer (TNBC), and despite the good initial response, resistance remains a major therapeutic obstacle. Here, we employed a High-Throughput Screen to identify targeted therapies that overcome chemoresistance in TNBC. We applied short-term paclitaxel treatment and screened 320 small-molecule inhibitors of known targets to identify drugs that preferentially and efficiently target paclitaxel-treated TNBC cells. to BV6 is mediated, at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…It is thus necessary to fully exploit paclitaxel-induced secreted death signals in a timely manner, as shown here using BH3 mimetics. Numerous preclinical studies, including ours, have put forth the benefits of combining antimitotic treatment with MOMP targeting by BH3 mimetics [46][47][48] . This study significantly enhances our mechanistic understanding of this combination by establishing a role for proapoptotic intercellular communications, particularly important in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus necessary to fully exploit paclitaxel-induced secreted death signals in a timely manner, as shown here using BH3 mimetics. Numerous preclinical studies, including ours, have put forth the benefits of combining antimitotic treatment with MOMP targeting by BH3 mimetics [46][47][48] . This study significantly enhances our mechanistic understanding of this combination by establishing a role for proapoptotic intercellular communications, particularly important in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-xL, another target of ABT-737, has been reported to be expressed in both responsive and nonresponsive tumors. In addition, administration of ABT-263, an orally available analog of ABT-737, following shortterm paclitaxel treatment has been found to be an effective therapeutic strategy for TNBCs using MDA-MB-231 cells [ 13 ]. Another study has reported that ABT-737 can engage mitochondrial apoptosis pathway to restore sensitivity to paclitaxel in breast cancer cell lines with acquired paclitaxel resistance [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a few preclinical studies have recently reported that ABT-737 has promising therapeutic effect as an adjunct with taxanes for Bcl-2 positive TNBCs [ 12 13 14 ], more validation studies are needed for its application in clinical practice. Therefore, the objective of this study was to validate the synergistic effect of ABT-737 on docetaxel using TNBC cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Navitoclax synergized with several chemotherapeutics in triple-negative breast cancer models (Oakes et al, 2012;Panayotopoulou et al, 2017) and non-small-cell lung carcinoma (NSCLC) and this is likely due to the targeting of BCL-XL (Leverson et al, 2015b;Xiao et al, 2015). Interestingly, a recent report found that navitoclax and venetoclax synergize with chemotherapeutics that can reduce MCL-1 levels (Inoue-Yamauchi et al, 2017), however, the underlying molecular mechanisms explaining the efficacy of combinations may vary with different drugs.…”
Section: Impact Of Combinations Of Bh3-mimetics With Standard-of-carementioning
confidence: 99%